Factors that Affect Brand Loyalty and Customer Advocacy: the Moderating Role of Greenwashing - Fathur Rosi; Ayu Ekasari (Journal of Social Research, 2023)
This study aims to determine and analyze the influence of green perceived value and altruistic value on customer engagement behavior, the influence of customer engagement behavior on brand loyalty and customer advocacy, test the role of mediation between green perceived value and altruistic value on brand loyalty and test the role of moderation greenwashing perception between green perceived value and altruistic value towards brand loyalty. The data collection technique method uses nonprobability sampling with a purposive sampling method. The data was collected directly from a sample that had adjusted the criteria and disseminated through a questionnaire to 120 respondents using a Likert scale of 1-5 where 1 indicated strong disapproval, while 5 indicated strongly agreed. The statements in this study consist of 20 statements obtained from six variables, namely the variables green perceived value, altruistic value, brand loyalty, customer advocacy, customer engagement behavior, and greenwashing perception. The questionnaire was distributed through a google form to respondents who had consumed Aqua and Le Minerale bottled drinking water (AMDK). The analysis method used in this study is the Structural Equation Model (SEM). The results showed that green perceived value has a positive effect on customer engagement behavior, altruistic value has a positive effect on customer engagement behavior, customer engagement behavior has a positive effect on brand loyalty, customer engagement behavior has a positive effect on customer advocacy, Customer Engagement Behavior Mediates the Influence Between Green Perceived Value on Brand Loyalty, Customer Engagement Behavior Mediates the Influence Between Altruistic Value and Brand Loyalty, Greenwashing Perception Moderates the Influence of Green Perceived Value on Brand Loyalty and Greenwashing Perception Results moderating the influence of altruistic values on brand loyalty.